Problems of Criminal Online Trial System and the Path to Improve - Lei, Aomi; Luo, Qingqing (Transactions on Social Science, Education and Humanities Research, 2023)
Criminal online court hearings have the unique value of improving the efficiency and quality of litigation, but their development has been relatively slow compared to civil online litigation. Due to the fragmentation and vagueness of the relevant provisions, the limits of their application are unclear, and there are debates on the limitation or expansion; there are still gaps in how to exercise the right of procedural choice and how to raise and resolve objections to procedural choice; it is difficult to guarantee the confidentiality of communication between the defendant and the defense, and there are difficulties in exercising the pre-trial rights of the defense. In order to improve the remaining defects, the limits of application of criminal online court trial should be expanded to summary procedures, ordinary procedures and minor criminal cases with little controversy, excluding the application of complex and difficult cases, the use of "special reasons" should be justified; the choice of procedures and objections should be made in writing, and the court will make a decision on procedural changes after verification and review of the objections; It should guarantee the confidentiality of defense communication from the meeting session, facilitate the exercise of the defense's right to read the file and investigate and obtain evidence, and promote the realization of the defense rights of the defendant in the online trial.